Pinheiro, P. (2015). Aristóteles. Poética. Edição bilíngue. Tradução, Introdução e Notas. São Paulo, Editora 34 - Franco, Irley Fernandes (Revista Archai, 2016)
Resenha: Pinheiro, P. (2015). Aristóteles. Poética. Edição bilíngue. Tradução, Introdução e Notas. São Paulo. Editora 34